Effects of labour costs on different branches of service production in Benin - Houndjo, André (Future Science / FSH-PH Publications, 2023)
The study's objective is to evaluate the influence of labour costs on the output of the service sector industries, particularly in the following industries: trade, transport and communication, hotels and restaurants. Inspired by the work of the BLS, we have constructed the labour cost index for the Eurozone, a very high-frequency indicator that will allow us to achieve our objective. The analysis was done over eight years, from the different quarters of 2014 to the third quarter of 2021. Using linear regression, it explores the relationships between the value added of the branches and other variables such as the labour cost index and credit to the economy. To this end, we conducted several tests that allowed us to opt for an error correction model (ECM). The results revealed that labour costs positively influence the firms’ output in the different sectors under study.